2021
DOI: 10.1002/jdd.12824
|View full text |Cite
|
Sign up to set email alerts
|

US students’ perceptions on environmental sustainability in dental school

Abstract: Objectives At present, there are no published reports assessing pre‐doctoral curricular experience or participatory involvement with Environmental Sustainability in Dentistry (ESD) in the United States. This study aims to assess whether students enrolled in US dental schools receive any training with ESD and gauge dental students’ level of interest and attitudes regarding ESD within their dental education. Methods A descriptive cross‐sectional study utilizing a 16‐questions validated survey was conducted on Qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 12 publications
4
14
0
Order By: Relevance
“…The findings were consistent with previously published studies in the literature that have explored this topic [ 16 , 17 ]. Gershberg et al conducted a cross-sectional study including 378 dental students from 17 dental schools in the United States [ 17 ].…”
Section: Discussionsupporting
confidence: 93%
“…The findings were consistent with previously published studies in the literature that have explored this topic [ 16 , 17 ]. Gershberg et al conducted a cross-sectional study including 378 dental students from 17 dental schools in the United States [ 17 ].…”
Section: Discussionsupporting
confidence: 93%
“…The findings were consistent with previously published studies in the literature who has explored this topic [15,16]. Gershberg et al conducted a cross-sectional study including 378 dental students from 17 dental schools in the United States [16].…”
Section: Discussionsupporting
confidence: 89%
“…The findings were consistent with previously published studies in the literature who has explored this topic [15,16]. Gershberg et al conducted a cross-sectional study including 378 dental students from 17 dental schools in the United States [16]. Despite the low response rate (5%), they found that although the majority of students thought that ESD is important, the majority of them were 'slightly' to 'not at all' knowledgeable about it.…”
Section: Discussionsupporting
confidence: 86%
“…There is a growing recognition of the need to urgently raise awareness of sustainability at the formative stage of individual's professional education. This requires the integration of concepts and remediation strategies in the undergraduate curricula of dental education, with current important pioneering work highlighting academic progress and student representation [47,48,49].…”
Section: Educationmentioning
confidence: 99%
“…In the oral healthcare undergraduate curricula, there is a need to increase awareness and sustainable impactful actions through carefully channelled educational programmes, a process that is currently underway that considers how sustainability can be included in the undergraduate dental curriculum [47,48,49]. This needs to be provided from an early point in the curriculum with an opportunity to share best practice with other dental schools.…”
Section: Oral Health Professional Educationmentioning
confidence: 99%